2020
DOI: 10.3389/fphar.2020.00167
|View full text |Cite
|
Sign up to set email alerts
|

Pentameric Ligand-Gated Ion Channels as Pharmacological Targets Against Chronic Pain

Abstract: Chronic pain is a common detrimental condition that affects around 20% of the world population. The current drugs to treat chronic pain states, especially neuropathic pain, have a limited clinical efficiency and present significant adverse effects that complicates their regular use. Recent studies have proposed new therapeutic strategies focused on the pharmacological modulation of G-protein-coupled receptors, transporters, enzymes, and ion channels expressed on the nociceptive pathways. The present work inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 76 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…In agreement with this concept, a recent study in rats found that diazepam reverted the toxicity induced by gelsenicine, another Gelsemium alkaloid ( Li et al, 2022 ). Further studies on inhibitory receptors may generate a rational framework to design targeted pharmacological approaches to treat acute Gelsemium alkaloid toxicity through, for example, positive allosteric modulators of GlyRs or of GABA A Rs ( Lara et al, 2020 ; Cerne et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this concept, a recent study in rats found that diazepam reverted the toxicity induced by gelsenicine, another Gelsemium alkaloid ( Li et al, 2022 ). Further studies on inhibitory receptors may generate a rational framework to design targeted pharmacological approaches to treat acute Gelsemium alkaloid toxicity through, for example, positive allosteric modulators of GlyRs or of GABA A Rs ( Lara et al, 2020 ; Cerne et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We performed molecular docking assays using the structures available for GlyRs and GABA A Rs to start the molecular examination of the alkaloid’s interaction with these ion channels [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Due to their relevance as the structural domains responsible for binding agonists, antagonists, and allosteric modulators [ 24 ], the docking procedures focused on the extracellular domain (ECD) and transmembrane domains (TMD). Our bioinformatic assays revealed that a major percentage of the alkaloid–GlyR (≈81–95%) and alkaloid–GABA A R (≈74%) complexes were located on the receptor ECD, while few interactions were positioned on the TMDs ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxychloroquine was also active on modulating ion channel receptors (bioactivity : 0.30). Ligand-dependent ion channels are also pharmacological targets for the development of new therapies 36 . For receptors of kinase inhibitors, the bioactivity of hydroxychloroquine is 0.44).…”
Section: Prediction Of Bioactivitymentioning
confidence: 99%